Model Pembelajaran Smart and Fun Education untuk Pembelajaran Sistem Periodik Unsur Berbasis Kurikulum 2013 - Dwi Susilo (LPPM STAI La Tansa Mashiro, 2013)
Curriculum 2013 emphasizes modern pedagogical dimension in learning, using a scientific approach. The learning model Smart and Fun Education (SAFE) has the characteristics of intelligent learning and fun, as the meaning of the word smart and fun. This learning model rests on multiple intelligence (multiple intelligence) and visual learning modalities, auditory and kinesthetic. SPU or the periodic table of chemical elements is a learning material for students of class X High school. SAFE learning models provide a learning experience for all types of learning modalities. From the analysis and discussion, it can be concluded that: 1) learning model Smart and Fun Education in accordance with the scientific approach, 2) learning model Smart and Fun Education students using active learning strategies (ative learning); 3) SAFE Learning model is ideal to use to teach SPU based curriculum 2013.